Pushing the efficiency of high open-circuit voltage binary organic solar cells by vertical morphology tuning - Cai, Guilong (2023)
The tuning of vertical morphology is critical and challenging for organic solar cells (OSCs). In this work, a high open-circuit voltage (VOC ) binary D18-Cl/L8-BO system is attained while maintaining the high short-circuit current (JSC ) and fill factor (FF) by employing 1,4-diiodobenzene (DIB), a volatile solid additive. It is suggested that DIB can act as a linker between donor or/and acceptor molecules, which significantly modifies the active layer morphology. The overall crystalline packing of the donor and acceptor is enhanced, and the vertical domain sizes of phase separation are significantly decreased. All these morphological changes contribute to exciton dissociation, charge transport, and collection. Therefore, the best-performing device exhibits an efficiency of 18.7% with a VOC of 0.922 V, a JSC of 26.6 mA cm-2 , and an FF of 75.6%. As far as it is known, the VOC achieved here is by far the highest among the reported OSCs with efficiencies over 17%. This work demonstrates the high competence of solid additives with two iodine atoms to tune the morphology, particularly in the vertical direction, which can become a promising direction for future optimization of OSCs.